2014
DOI: 10.1002/jms.3420
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope ratios of H, C, N and O in Italian citrus juices

Abstract: Stable isotope ratios (SIRs) of C, N, H and O have been exensively used in fruit juices quality control (ENV and AOAC methods) to detect added sugar and the watering down of concentrated juice, practices prohibited by European legislation (EU Directive 2012/12). The European Fruit Juice Association (AIJN) set some reference guidelines in order to allow the judging of the genuiness of a juice. Moreover, various studies have been carried out to determine the natural variability of SIRs in fruit juices, but none … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…As reported for other plant products, such as olive oil, or orange juice, in cocoa beans δ 2 H is correlated with δ 18 O (Fig. ).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…As reported for other plant products, such as olive oil, or orange juice, in cocoa beans δ 2 H is correlated with δ 18 O (Fig. ).…”
Section: Resultssupporting
confidence: 75%
“…More recently, 1 H NMR spectra of traded cocoa beans were used to characterise fermented cocoa beans on the basis of the variety and geographical origin. [15,16] H, C, N, O and S stable isotope ratios measured using Isotope Ratio Mass Spectrometry (IRMS) have been shown to be a reliable tool for establishing the authenticity of a wide variety of food products, such as wine, [17] olive [18] and sesame oils, [19] orange juice, [20] honey, [21] beef, [22] fish, [23,24] shrimps [25] and prawns, [26] ham, [27] milk, [28] rice, [29] lentils. [30] This is due to particular isotopic fractionation processes, which reflect both climatic phenomena (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile organic compounds (VOCs) in citrus juice are a class of secondary metabolites produced. It has been found that sweet orange juice and mandarin juice have different VOCs [25][26][27], and the difference between them can be used to identify whether orange juice contains excessive mandarin juice. Given this, we have collected a full range of varieties of citrus that can be used for juicing and prepared them into NFC citrus juice.…”
Section: Introductionmentioning
confidence: 99%
“…9 These isotopic ratio techniques have been widely applied to identification of geographical origin as well as to authentication/ traceability of sparkling and non-sparkling beverages such as ciders, [10][11][12] beer, 13 juice 14 and wine. 15,16 According to the Brazilian legislation 17 (decree No.…”
Section: Introductionmentioning
confidence: 99%